2016
DOI: 10.1590/1981-6723.7315
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de chocolate branco com extrato de erva-mate

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Desenvolvimento de chocolate branco com extrato de erva-mateDevelopment of white chocolate with yerba mate extract ResumoO chocolate é um produto apreciado mundialmente e as tendências do setor apontam para a busca de inovações e a procura por produtos mais saudáveis. Da mesma for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…Diante disso, tem-se aumentado o desenvolvimento de produtos à base de erva-mate, para atender à demanda dos consumidores (CHIESA et al, 2012;PRECI et al, 2011;ZANCHETT et al, 2016).…”
Section: Introductionunclassified
“…Diante disso, tem-se aumentado o desenvolvimento de produtos à base de erva-mate, para atender à demanda dos consumidores (CHIESA et al, 2012;PRECI et al, 2011;ZANCHETT et al, 2016).…”
Section: Introductionunclassified
“…The color of cookies with LJ extracts became darker with an increased level of LJ extracts ( Figure 6 ), which caused the lower scores of cookie color. Color, as a key visual factor, is vital for food appearance [ 24 ], and the darker color of cookies with a higher proportion of LJ extracts led to lower overall acceptance. When the level of LJ extracts reached 4%, the flavor, color and appearance score of cookies significantly decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Zanchett et al 19 added yerba-mate in white chocolate, and the results showed that the product was well accepted and the yerba-mate extract gave white chocolate compounds with antioxidant action. In Coró et al 48 the lipid oxidation in the jerked beef meat product was evaluated using extract of wild herb and propolis.…”
Section: New Food Products With Yerba-mate Extractmentioning
confidence: 99%
“…The use of yerba-mate extracts in the development of new products with technological potential has been highlighted 17 , both in the food and pharmaceutical industries. Research developed over the years has sought to turn common foods into functional foods by adding yerba-mate extracts [18][19][20][21][22][23][24] . Studies have shown that the inclusion of yerba-mate in the diet improves the immune system, reduces oxidative stress, improves cholesterol and triglycerides [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%